Blood Lead Concentrations in Leather-Industry Workers Compared with Community Controls: A Cross-Sectional Study - Tahir, Amina; Ashraf, Saima; Esha, Urwa Tul; Sughra, Manahal; Shehzadi, Abida; Ashraf, Sadia (Biological and Clinical Sciences Research Journal, 2025)
Leather processing involves potential lead exposure, yet biomonitoring data from Pakistani workers are limited. Objective: To compare blood lead concentrations between leather-industry workers and community controls in Sialkot, Pakistan. Methods: This analytical cross-sectional study enrolled 80 adults, comprising 40 tannery workers and 40 controls without known occupational heavy-metal exposure. Venous whole blood samples were collected in heparinized tubes, digested with nitric acid/hydrogen peroxide, and analyzed for lead (Pb) concentrations using inductively coupled plasma–optical emission spectrometry with multi-point external calibration. The primary outcome was blood lead level (µg/dL). Group means were compared using two-sided statistical tests with significance set at α=0.05. Results: Tannery workers demonstrated significantly higher blood lead levels compared with controls (0.441 ± 0.8947 vs −0.0225 ± 0.0800 µg/dL; p=0.0016). Among workers, concentrations ranged from −0.01 to 4.05 µg/dL, with the highest level observed in the 40–50-year age group. Minor negative values reflected blank subtraction near the detection limit. Conclusion: Employment in the leather industry was associated with significantly elevated blood lead concentrations relative to community controls. These findings highlight the need for workplace exposure controls and routine biomonitoring to safeguard worker health in this sector.